Survival analysis of Malaysian women with breast cancer: results from the University of Malaya Medical Centre - Mohd Taib, N.A.; Yip, C.H.; Mohamed, I. (West Asia Organization for Cancer Prevention, 2008)
The overall survival in our centre was low. Recognizing factors that affect prognosis of breast cancer patients in Malaysia may improve delivery of health care to at-risk groups by strategizing interventions as survival depends on early detection and effective treatment.